2003
DOI: 10.1023/a:1022003126168
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of PTSD following the violent death of a child and predictors of change 5 years later

Abstract: In this study, we examined the violent death bereavement trajectories of 173 parents by following them prospectively for 5 years after their children's deaths by accident, suicide, homicide, or undetermined causes. Using latent growth curve methodology, we examined how the initial level of PTSD and the rate of change over time were influenced by 9 predictors: the deceased children's causes of death, parents' gender, self-esteem, 3 coping strategies, perceived social support, concurrent levels of mental distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 29 publications
6
100
2
2
Order By: Relevance
“…Scientific evidence points in different directions (Cohen & Mc.Kay, 1984) due to the different perspectives from which we have studied the relationship between SS and grief such as gender (Bankoff, 1983;Goodkin et al, 1998;Riley, LaMontagne, Hepworth & Murphy, 2007), relationship to the deceased (Bankoff, 1983;Murphy, Johnson, Chung & Beaton, 2003;Ott, 2003;Ott, Kelber & Blaylock, 2010;Riley et al, 2007;. Somhlaba & Wait, 2008;Stroebe et al, 2005), cause of death (Burke et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific evidence points in different directions (Cohen & Mc.Kay, 1984) due to the different perspectives from which we have studied the relationship between SS and grief such as gender (Bankoff, 1983;Goodkin et al, 1998;Riley, LaMontagne, Hepworth & Murphy, 2007), relationship to the deceased (Bankoff, 1983;Murphy, Johnson, Chung & Beaton, 2003;Ott, 2003;Ott, Kelber & Blaylock, 2010;Riley et al, 2007;. Somhlaba & Wait, 2008;Stroebe et al, 2005), cause of death (Burke et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%
“…The first includes studies that support the contribution of SS in decreasing the symptoms of grief: reduction of depression (Burke et al, 2010), anxiety (Somhlaba & Wait, 2008) and/or post-traumatic stress (Murphy et al, 2003;Vanderwerker & Prigerson, 2003). For example, people bereaved because of homicide (Burke et al, 2010), and bereaved mothers (Riley et al, 2007) both showed fewer symptoms associated with grief.…”
Section: Introductionmentioning
confidence: 99%
“…Vanhempien toivoma tuki sisältää aineettoman, mutta myös hyvin konkreettisen tuen saamisen sekä läheisiltä, että ammattilaisilta. Lapsen kuolema vaikuttaa yksilötasolla van hempien hyvinvointiin elämänlaatua heikentäen (2) ja erilaisia terveysongelmia aiheuttaen (2)(3)(4)(5). Tämän lisäksi lapsen kuoleman vaikutukset ulot tuvat myös sosiaalisiin suhteisiin, perhedyna miikkaan ja erityisesti parisuhteeseen (3,(6)(7)(8).…”
Section: Sosiaalilääketieteellinen Aikakauslehti 2017: 54: 121-133unclassified
“…Significant trauma can also emerge from the families' experiences of the criminal justice system (CJS) which bears down on their lives in an apparent attempt to provide redress and accountability for the crime. Indeed, the CJS can create a form of 'secondary victimisation' for families who become disempowered, distressed and dictated to by the criminal justice process (Asaro, 2001a;Burgess, 1975;Casey, 2011;Mezey et al, 2002;Murphy et al, 2003;Rock, 1998). These experiences of the families of homicide victims have been reasonably well charted in the academic literature but what is uncharted and unknown is the effect of homicide and the CJS on families when no person has been convicted for the crime.…”
Section: Introductionmentioning
confidence: 99%